Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Metcalf, Ginger A; Muzny, Donna M; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Gibbs, Richard A; Boerwinkle, Eric (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, André; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.